Neandertal features of the deciduous and permanent teeth from Portel‐Ouest Cave (Ariège, France). Issue 1 (21st November 2018) - Becam, Gaël; Chevalier, Tony
Abstract: Objectives: We describe 14 unpublished and nine published teeth from the Mousterian level of Portel‐Ouest (Ariège, France), dated to 44 ka. In a comparative context, we explore the taxonomical affinities of those teeth with Neandertals and modern humans which are both known to exist at that time. We further make some paleobiological inferences about this human group. Methods: The comparative analysis of Neandertals and modern humans is based on nonmetric traits at the outer enamel surface and the enamel–dentine junction, crown diameters and three‐dimensional (3D) enamel thickness measurements of lower permanent teeth. The crown and roots are explored in detail based on the μCT‐scan data to identify the multiple criteria involved in the paleobiological approach. Results: Nonmetric traits and 3D enamel thickness tend to be more similar to Neandertals than modern humans, notably for C1, P4, and M2 (included in all analyses) as well as volume of the pulp cavity in roots of the anterior permanent teeth. The Portel‐Ouest sample corresponds to a minimum of seven juveniles, one or two adolescents and one adult, which exhibit recurrent linear enamel hypoplasia (up to five events for one individual), the torsiversion of one anterior tooth and irregular oblique wear in some anterior deciduous teeth. Discussion: This morphological study confirms that the remains from Portel‐Ouest are Neandertals, associated with a Mousterian complex. Furthermore, we found the expected pattern of mortality and stress for a Neandertal group, that is, various age categories and developmental defects (nonexclusive to Neandertals), while adults are underrepresented and juveniles are overrepresented. Further excavations would contribute finding new remains and maybe complete this demographic profile.